Individual and conflict in Greek ethics - White, Nicholas, 1942- (New York : Oxford university press, 2002)
Since the 18th century, philosophers wishing to oppose the supposed dualism of rationality or morality versus inclination have looked to Greek thought for an alternative, resulting in the view of Greek ethics as the ethics of virtue.
Includes bibliographical references and index.
Keywords: Ethics -- Greece; Ethics -- History; Electronic books